Projeto de um guia de fontes eletrônicas brasileiras em biblioteconomia - CORREA, Anderson Rodrigo da Costa (2017)
Presents a project of a guide of Brazilian electronic sources in Librarianship. It proposes as a general objective to elaborate a guide with the Brazilian electronic sources in librarianship and specific that aims to present in the guide the electronic resources such as: databases, blogs and portals, electronic periodicals, books, thesaurus and to inform on national, regional, public examinations, undergraduate and postgraduate courses. In order to carry out the work, the bibliographic research was used in order to provide a theoretical basis for the study, and to search websites for their study, in order to analyze whether the websites follow the criteria for electronic guides. It discusses concepts and links the areas of Information Science and Librarianship. It expounds in a non-exhaustive way the origin of librarianship and Information Science. Describes briefly the concepts of sources of information. Explains prominently what guides are from sources of information. Relates the criteria for the elaboration of source guides, listed by some authors. It addresses important points about the need for an electronic source guide. It talks about the dispersion of the literature and the insufficiency in the elaboration of instruments that compile the information of more consistent form and easy to recover. The conclusion made a synthesis of the search for the universalization of knowledge and compilation, due to the explosion of information, an idea that emerged in the sixteenth century with Conrad Gesner and the book Universalis Library, proposes the elaboration of a project in the same line of action for the Faculty of Library Science Federal University of Pará.